Directional electromagnetic steel sheet

JP7639661B2Active Publication Date: 2025-03-05JFE STEEL CORP
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
JP2021182197
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-11-08
Publication Date
2025-03-05
Estimated Expiration
2041-11-08

AI Technical Summary

Benefits of technology

【0026】 本発明によれば、溶融凝固部を線状に形成した耐熱型磁区細分化方向性電磁鋼板において、磁束密度の劣化をまねくことなしに、鉄損の大幅な低減を実現することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639661000004
    Figure 0007639661000004
  • Figure 0007639661000005
    Figure 0007639661000005
  • Figure 0007639661000006
    Figure 0007639661000006
Patent Text Reader

Abstract

To establish a magnetic domain segmentation technique using a melt-solidified part without causing deterioration of magnetic permeability.SOLUTION: A grain-oriented electrical steel sheet has front and back sides, at least one of which has a melt-solidified part extending across the sheet in its rolling direction, wherein the melt-solidified part has a composition and a magnetic permeability different from those of the matrix phase of the grain-oriented electrical steel sheet.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a grain-oriented electrical steel sheet suitable as an iron core material for wound core transformers and the like. [Background technology]

[0002] Grain-oriented electrical steel sheets are used, for example, as materials for the iron cores of transformers. In such transformers, it is necessary to suppress energy loss and noise, and the energy loss is influenced by the iron loss of the grain-oriented electrical steel sheets, while the noise is influenced by the magnetostriction characteristics of the grain-oriented electrical steel sheets. In recent years, there has been a strong demand for reducing energy loss in transformers and noise during operation in order to comply with energy conservation and environmental regulations, making it extremely important to develop grain-oriented electrical steel sheets with good core loss and magnetostriction properties.

[0003] Here, the iron loss of grain-oriented electrical steel sheet is mainly composed of hysteresis loss and eddy current loss. Methods developed to improve hysteresis loss include highly orienting the (110)

[0001] orientation, known as the GOSS orientation, in the rolling direction of the steel sheet and reducing impurities in the steel sheet. Methods developed to improve eddy current loss include increasing the electrical resistance of the steel sheet by adding Si and applying coating tension in the rolling direction of the steel sheet. However, there are manufacturing limitations to these methods when pursuing further reduction in iron loss of grain-oriented electrical steel sheet.

[0004] Therefore, magnetic domain refinement technology has been developed as a method to further reduce iron loss in grain-oriented electrical steel sheets. Magnetic domain refinement technology is a method to reduce iron loss, especially eddy current loss, in grain-oriented electrical steel sheets by introducing non-uniformity in magnetic flux through physical methods such as forming grooves or introducing localized distortion into steel sheets after final annealing or baking of the insulating coating, thereby refining the width of the 180° magnetic domains (main magnetic domains) formed along the rolling direction.

[0005] For example, Patent Document 1 proposes a technology for improving iron loss, which was 0.80 W / kg or more, to 0.70 W / kg or less by introducing linear grooves with a width of 300 μm or less and a depth of 100 μm or less into the surface of a steel sheet. Patent Document 2 also proposes a technology for improving iron loss, which was 0.80 W / kg or more, to 0.70 W / kg or less by irradiating a plasma flame in the sheet width direction of the surface of a steel sheet after secondary recrystallization and introducing localized thermal strain, when the magnetic flux density (B8) of the steel sheet is 1.935 T when excited with a magnetizing force of 800 A / m, and the iron loss (W 17 / 50 A method has been proposed to improve this to 0.680 W / kg.

[0006] The technique of forming linear grooves as described in Patent Document 1 is called heat-resistant magnetic domain refinement because the magnetic domain refinement effect does not disappear even when stress relief annealing is performed after core forming. Here, methods proposed for forming grooves in grain-oriented electrical steel sheets include, for example, an electrolytic etching method in which grooves are formed on the surface of a steel sheet by electrolytic etching (see Patent Document 2), a laser method in which a high-power laser is used to locally melt and evaporate the steel sheet (see Patent Document 3), and a gear press method in which a gear-shaped roll is pressed against a steel sheet to create an indentation (see Patent Document 4).

[0007] In these techniques, it is possible to obtain an excellent iron loss improvement effect by forming deeper grooves or indentations. However, making the grooves or indentations deeper leads to deterioration of the sheet passing property and the magnetic permeability of the steel sheet, so it is known that there is a limit to the iron loss improvement effect when used alone.

[0008] It is generally known that the magnetic domain refinement effect of conventional grooves is greater the larger the surface area of ​​the groove end of the steel sheet. However, when grooves are formed deep in the sheet thickness direction, the increased groove volume not only deteriorates the magnetic properties of the steel sheet, such as a decrease in magnetic flux density, but also increases manufacturing disadvantages such as breakage. Therefore, in conventional heat-resistant magnetic domain refinement materials, the depth of groove formation is limited, making it difficult to obtain a sufficiently high iron loss improvement effect.

[0009] To solve this problem, Patent Document 5 proposes a method of forming grooves in a steel sheet and then filling the grooves with a magnetic metal or its alloy. In this method, the deterioration of magnetic flux density due to the formation of the grooves can be suppressed by filling the grooves with a magnetic material.

[0010] However, this conventional method is premised on providing grooves in the steel sheet, and therefore there is a limit to the improvement in iron loss. In addition, there is a disadvantage in that magnetostriction deteriorates due to distortion caused by the difference in lattice constant between the metal filled in the grooves and the steel sheet parent phase.

[0011] On the other hand, in the method of introducing thermal strain as described in Patent Document 6, the effect of introducing thermal strain is not obtained by strain relief annealing, and therefore this method is called non-heat-resistant magnetic domain refinement. Here, non-heat-resistant magnetic domain refinement can significantly reduce eddy current loss by introducing local strain into the steel sheet. On the other hand, non-heat-resistant magnetic domain refinement is known to have a limit to the improvement in iron loss by itself, since the introduction of such strain leads to deterioration of hysteresis loss and magnetostriction.

[0012] Patent Document 7 also proposes forming a molten solidified line by irradiating a laser beam and using the molten solidified line to subdivide magnetic domains. This molten solidified line is formed by melting and solidifying the base steel of a grain-oriented electrical steel sheet with a laser beam, and since magnetic domains can be subdivided without forming recesses such as grooves, this has the advantage of being able to avoid the problems caused by the formation of grooves.

[0013] However, there was room for improvement in that the effect of reducing iron loss was smaller than that of conventional heat-resistant magnetic domain refinement methods such as groove formation. In other words, the molten solidified portion has the same composition as the parent phase or a composition that contains a small amount of the insulating coating formed on the steel sheet surface, and the microscopic difference in magnetic permeability at the interface between the parent phase and the molten solidified portion phase is small, making it difficult to further improve the magnetic domain refinement effect. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] Special Publication No. 6-22179 [Patent Document 2] JP 2012-77380 A [Patent Document 3] JP 2003-129135 A [Patent Document 4] Japanese Patent Application Publication No. 62-86121 [Patent Document 5] Japanese Patent Application Publication No. 5-186827 [Patent Document 6] Japanese Patent Application Publication No. 7-192891 [Patent Document 7] Japanese Patent Application Publication No. 6-212275 Summary of the Invention [Problem to be solved by the invention]

[0015] As described above, when applying the magnetic domain refining technology using the molten solidified portion to the development of a heat-resistant magnetic domain refined material with even higher properties, the magnetic permeability becomes an issue. Therefore, in order to develop a heat-resistant magnetic domain refined material with even higher properties, it is necessary to develop a new method from the viewpoint of magnetic permeability that can obtain a high magnetic domain refinement effect. Therefore, the object of the present invention is to establish this new method. [Means for solving the problem]

[0016] The inventors have conducted extensive research to solve the above problems. Magnetic domain refinement technology utilizes the fact that the width of the main magnetic domain of a steel sheet is refined by forming magnetic poles at the interface of the steel sheet where the magnetic permeability differs greatly in the rolling direction due to grooves or thermal distortion, and reducing the magnetostatic energy increased by these magnetic poles. In conventional heat-resistant magnetic domain refinement materials using grooves, the gaps in the grooves are used as the areas with different magnetic permeability. These gaps do not change even when stress relief annealing is performed, so the magnetic domain refinement effect is maintained. However, the presence of these gaps also deteriorates the magnetic permeability (magnetic flux density) of the entire steel sheet.

[0017] On the other hand, in non-heat-resistant magnetic domain refinement, thermal distortion is introduced by irradiating an energy beam. The residual stress generated by this thermal distortion creates new magnetic domains (closure domains) with magnetization components in the (100) or (010) direction perpendicular to the rolling direction (001). At this time, the magnetization directions of the main magnetic domains and the closure domains are different, so a local change in magnetic permeability occurs in the rolling direction, resulting in magnetic domain refinement. This thermal distortion is eliminated by strain relief annealing, so the magnetic domain refinement effect also disappears by strain relief annealing. However, since both the main magnetic domains and closure domains are formed inside the grain-oriented electrical steel sheet, there is almost no change in magnetic flux density.

[0018] Therefore, in order to achieve heat-resistant magnetic domain refinement with lower core loss without degrading the magnetic flux density, it is considered important to form regions with locally different magnetic permeability in the steel sheet. We then investigated how to achieve this and found that it is advantageous to locally melt and solidify the steel sheet using an energy beam, and further found that it is possible to achieve localized changes in magnetic permeability by mixing a component system with a different magnetic permeability from the parent phase, specifically a metal element and / or a ceramic compound, during the melting and solidification process.

[0019] The present invention has been made based on the above findings. That is, the gist and configuration of the present invention are as follows. (1) A grain-oriented electrical steel sheet having a molten and solidified portion extending in a direction transverse to the rolling direction of the steel sheet on at least one of the front and back surfaces of the grain-oriented electrical steel sheet, the molten and solidified portion having a component composition and magnetic permeability different from those of a parent phase of the grain-oriented electrical steel sheet.

[0020] (2) The grain-oriented electrical steel sheet according to (1), wherein the molten and solidified portion contains a component having a magnetic permeability different from that of the parent phase.

[0021] (3) The grain-oriented electrical steel sheet according to (1) or (2), wherein the molten solidified portion contains one or more metal elements different from the parent phase.

[0022] (4) The grain-oriented electrical steel sheet according to (1), (2), or (3), wherein the molten and solidified portion contains a ceramic compound.

[0023] (5) The grain-oriented electrical steel sheet according to any one of (2) to (4), wherein the molten solidified portion has a content of a component having a magnetic permeability different from that of the parent phase of 5 mass% or more and 40 mass% or less.

[0024] (6) The grain-oriented electrical steel sheet according to any one of (1) to (5), wherein the molten solidified portions are formed periodically in the rolling direction, and the interval between the molten solidified portions in the rolling direction is 1 mm or more and 10 mm or less.

[0025] (7) The grain-oriented electrical steel sheet according to any one of (1) to (6), wherein the molten and solidified portion is linear. Effect of the Invention

[0026] According to the present invention, in a heat-resistant, domain-refined, grain-oriented electrical steel sheet in which a molten and solidified portion is formed in a linear shape, it is possible to realize a significant reduction in iron loss without causing a deterioration in magnetic flux density. [Brief description of the drawings]

[0027] [Figure 1] 1 is a graph showing the relationship between the content of components with different magnetic permeabilities and the relative magnetic permeability μr with respect to the parent phase. [Diagram 2] 1 is a graph showing the relationship between the content of components with different magnetic permeability and iron loss W17 / 50. [Diagram 3] 13 is a graph showing the relationship between the content of components with different magnetic permeabilities and the amount of change ΔB8 in magnetic flux density B8. [Figure 4] 1 is a graph showing the relationship between the content of components with different magnetic permeability and the magnetostrictive harmonic level MHL15 / 50. [Diagram 5] 1 is a graph showing the relationship between the molten solidified portion interval Lp and the relative magnetic permeability μr with respect to the parent phase. [Figure 6] 1 is a graph showing the relationship between the molten solidified portion interval Lp and iron loss W17 / 50. [Figure 7] 13 is a graph showing the relationship between the molten solidified portion interval Lp and the change amount ΔB8 of the magnetic flux density B8. [Figure 8] 1 is a graph showing the relationship between the molten solidified portion interval Lp and the magnetostrictive harmonic level MHL15 / 50. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] The experimental results that led to the completion of the present invention will now be described. [Experiment 1] A grain-oriented cold-rolled steel strip was produced through the cold rolling process according to the general manufacturing method for grain-oriented electrical steel sheets, and metal elements or ceramics were electrodeposited on a part of the surface at a desired thickness.The metal elements or ceramics used here were Ni, Co, Cr, Sn, Cu-Zn, Mg2SiO4, and SiO2. A laser was irradiated onto the surface of the part of the cold-rolled steel strip where the electrodeposition film was applied, and both the electrodeposition film and the steel sheet base metal in the irradiated area were melted and solidified. At this time, the laser was irradiated under conditions where the laser output density was 1 to 20 [J / m] as the ratio P / v of the deflection speed v and the laser output P. A single-mode fiber laser was used as the laser source, and no assist gas was used. The laser was irradiated linearly across the entire width in a direction perpendicular to the rolling direction of the cold-rolled steel strip. This irradiation was then repeated at 5 mm intervals in the rolling direction. In addition, the laser was also irradiated to the non-electrodeposited portion of the cold-rolled steel strip, where no electrodeposited film was present, to form a molten and solidified portion.

[0029] The cold-rolled steel strip after the laser irradiation had the remaining electrodeposition layer removed, was subjected to decarburization annealing, and was then coated with an annealing separator, wound into a coil, and subjected to final annealing. Next, flattening annealing was performed to form a tensile coating on the steel strip surface. Test pieces were cut out from the electrodeposited part irradiated with the laser (hereinafter also referred to as the electrodeposited part), the non-electrodeposited part irradiated with the laser (hereinafter also referred to as the non-electrodeposited part), and the non-irradiated part not irradiated with the laser (hereinafter also referred to as the non-irradiated part), and the magnetic properties, W, were measured by the Epstein method described in JIS C2550. 17 / 50 and B8 were measured. Then, the change in magnetic flux density B8, ΔB8 (=B8 of the electrodeposited or non-electrodeposited portion−B8 of the non-irradiated portion) was calculated from B8 of each test piece.

[0030] Here, W 17 / 50 means the iron loss value when alternating magnetization of 1.7 T, 50 Hz is applied in the rolling direction of the steel sheet, and B8 means the magnetic flux density when magnetized in the rolling direction with a magnetizing force of 800 A / m.

[0031] In addition, for each test piece cut out from the above-mentioned electrodeposited portion, non-electrodeposited portion, and non-irradiated portion, a hysteresis loop was measured, and the maximum magnetic permeability in the initial magnetization curve was measured. The ratio μ r (=μelectrodeposited portion / μnon-irradiated portion: hereinafter also referred to as "relative magnetic permeability to the parent phase") was calculated as an index of magnetic permeability change.

[0032] Furthermore, for each test piece, a laser Doppler magnetostriction vibrometer was used to measure the magnetostrictive vibration waveform when magnetized with a 1.5T, 50Hz sinusoidal AC current. This was Fourier-decomposed into vibration acceleration components with frequencies of 100Hz each, and the values ​​of each frequency component corrected for hearing on the A scale were integrated from 0 to 1000Hz to obtain an index of magnetostrictive properties, the magnetostrictive harmonic wave (MHL). 15 / 50 It was calculated as:

[0033] After completing each of the above measurements, the test pieces of the electrodeposited parts were embedded in a mold to include the molten solidified parts, and mirror polished. The amounts of the electrodeposited components in the molten solidified parts were analyzed using an EPMA, and the amounts were measured as the contents of components with different magnetic permeability from the non-molten solidified parent phase of the steel sheet (hereinafter, also referred to as components with different magnetic permeability). The relationship between the measured contents of components with different magnetic permeability and the above-mentioned various measured values ​​is shown in Figures 1 to 4.

[0034] That is, Fig. 1 shows the relationship between the content of components with different magnetic permeability and the relative magnetic permeability μ r Figure 2 shows the relationship between the content of different magnetic permeability components and iron loss W 17 / 50 FIG. 3 is a graph showing the relationship between the content of different magnetic permeability components and the change in magnetic flux density B8 ΔB8. FIG. 4 is a graph showing the relationship between the content of different magnetic permeability components and the magnetostriction harmonic level MHL. 15 / 50 4 is a graph showing the relationship between

[0035] First, looking at Figure 1, it can be seen that as the content of components with different magnetic permeability increases, the magnetic permeability decreases compared to that of the parent phase. On the other hand, in the sample (non-electrodeposited part) in which nothing was mixed into the molten solidified part, the magnetic permeability of the molten solidified part is about the same as that of the parent phase. In other words, by including a component with a different magnetic permeability in the molten solidified part, the magnetic permeability of the molten solidified part will be significantly different from that of the parent phase, and as a result, it is expected that the magnetic domain refinement effect will be enhanced.

[0036] It is also clear that the decrease in magnetic permeability is greater when non-magnetic metals (Cr, Sn, Cu-Zn) and ceramics (Mg2SiO4, SiO2) are included than when magnetic metals (Ni, Co) are included. This is thought to be because elements and compounds with lower magnetic permeability are mixed into the parent phase of the electrical steel sheet, which has a high magnetic permeability.

[0037] Furthermore, Fig. 2 shows that iron loss improves as the content of components with different magnetic permeability increases. This is thought to be because the above-mentioned decrease in magnetic permeability creates magnetic poles at the interface of the molten solidified part, resulting in a magnetic domain refinement effect. On the other hand, no improvement in iron loss is seen in the sample in which nothing was mixed into the molten solidified part (non-electrodeposited part). This is thought to be because, as shown in Fig. 1, the magnetic permeability of the molten solidified part was about the same as that of the parent phase, so no magnetic domain refinement effect was obtained.

[0038] Here, in order to have a significant difference in iron loss improvement compared to the non-electrodeposited part, the content of components with different magnetic permeability is preferably 5 mass% or more. This is because it is believed that when the magnetic permeability of the molten and solidified part is reduced by 5% or more compared to the magnetic permeability of the parent phase, magnetic poles are formed at the phase interface, and magnetic domain refinement occurs.

[0039] On the other hand, Fig. 3 shows that when the content of components with different magnetic permeability exceeds 40 mass%, B8 drops significantly. This is thought to be because the increase in low magnetic permeability parts makes it difficult to magnetize the steel sheet.

[0040] Furthermore, Fig. 4 shows that the magnetostriction harmonic level increases when the content of components with different magnetic permeability exceeds 40 mass%. This is thought to be because the increase in the content of components with different magnetic permeability increases the difference in lattice constant with the parent phase, causing strain to occur inside the steel sheet.

[0041] Based on the above results, it was concluded that in order to realize low magnetostriction and high magnetic permeability while exhibiting a high low iron loss effect, it is effective to mix a component having a magnetic permeability different from that of the parent phase, particularly a metal element and / or ceramics having a magnetic permeability lower than that of the parent phase, into the molten solidified portion. In particular, if the content of the component having a magnetic permeability different from that of the parent phase is 5 mass% or more, a remarkable effect in improving the iron loss is achieved. On the other hand, from the viewpoint of magnetic flux density and noise, it is preferable that the content of the component having a magnetic permeability different from that of the parent phase is 40 mass% or less. A more preferable content is 30 mass% or less.

[0042] [Experiment 2] As in the above-mentioned Experiment 1, silica (SiO2) was partially electrodeposited on a cold-rolled steel strip of directional electrical steel, and an electron beam was irradiated to the electrodeposited portion in a direction perpendicular to the rolling direction of the cold-rolled steel strip to form a molten solidified portion. At this time, the amount of electrodeposition and the intensity of the electron beam irradiation were set so that the content of silica, which is a component with a different magnetic permeability from the parent phase, was 20 mass%. In addition, the irradiation pattern of the electron beam was set to a sine wave with the scanning direction as the center of the amplitude, a linear uninterrupted irradiation, and a linear and dashed line pattern, and the formation interval of the molten solidified portion in the rolling direction (hereinafter also referred to as the molten solidified portion interval) Lp was changed between 0.5 and 11 mm. In addition, a laser was irradiated to some non-electrodeposited portions to form a molten solidified portion. The electrodeposited layer was removed from this cold-rolled steel strip, and after decarburization annealing, an annealing separator was applied, wound into a coil, and final annealing was performed. Next, flattening annealing was performed to form a tensile coating on the steel sheet surface. From the obtained steel strip, μ r , W 17 / 50 , ΔB8, MHL 15 / 50 was calculated.

[0043] The relationship between the molten solidified portion interval Lp and the above-mentioned various measured values ​​is shown in Figs. 5 to 8. That is, Fig. 5 shows the relationship between the molten solidified portion interval Lp and the relative magnetic permeability μ r Fig. 6 shows the relationship between the molten solidification interval Lp and the iron loss W 17 / 50 FIG. 7 is a graph showing the relationship between the molten solidified portion interval Lp and the change in magnetic flux density B8, and FIG. 8 is a graph showing the relationship between the molten solidified portion interval Lp and the magnetostriction harmonic level MHL 15 / 50 4 is a graph showing the relationship between

[0044] First, looking at Figure 5, the relative permeability μ r was lower when the electron beam irradiation pattern was a sine wave or straight line than when the irradiation pattern was the dashed line. This is thought to be because with the dashed line pattern, there are fewer areas mixed with components with low magnetic permeability in the direction in which the molten solidified part is formed (direction perpendicular to the rolling direction). In addition, in both irradiation patterns, the narrower the molten solidified part interval Lp, the lower the relative magnetic permeability μ rThis is believed to be due to an increase in the volume of the region with low magnetic permeability.

[0045] Next, looking at Fig. 6, the iron loss W 17 / 50 is decreased. This is thought to be because, in the sine wave pattern, the angle between the magnetization direction of the main magnetic domain and the molten solidified part increases, and the amount of magnetic poles formed at the interface does not increase efficiently. In addition, in both patterns, a tendency was confirmed for iron loss to improve as the interval Lp between the molten solidified parts becomes narrower. This is thought to be because the increase in the molten solidified part per unit length in the rolling direction increases the amount of magnetic poles formed, improving the effect of magnetic domain refinement. However, when the interval Lp between the molten solidified parts is 0.5 mm, iron loss increases. This is thought to be because the hysteresis loss deteriorates due to the excessive formation of molten solidified parts with low magnetic permeability on the steel sheet surface.

[0046] In addition, looking at Figures 7 and 8, ΔB8 and MHL 15 / 50 Although the influence of the formation pattern of the molten solidified portion is small, a tendency for deterioration was observed when the molten solidified portion interval Lp was 0.5 mm. The inventors consider this tendency as follows. In other words, for ΔB8, it is considered that the occupancy rate of the low magnetic permeability area on the steel plate surface increased due to the narrowing of the formation interval of the molten solidified part, and a large amount of energy was required to magnetize the steel plate. 15 / 50 It is believed that this is because the volume of strain introduced into the steel plate increases by narrowing the formation interval Lp of the molten solidified portion.

[0047] 5 to 8, it can be seen that a grain-oriented electrical steel sheet having better properties can be obtained when the formation interval Lp of the molten solidified portion is 1 mm or more and 10 mm or less. Similarly, it was revealed that it is particularly advantageous to form the formation pattern of the molten solidified portion in a straight line shape or a broken line shape.

[0048] Hereinafter, preferred embodiments of the present invention will be described in detail. However, the present invention is not limited to the configurations disclosed in the present embodiments, and various modifications are possible without departing from the spirit of the present invention.

[0049] [Grain-oriented electrical steel sheet] In the present invention, the composition of the slab for grain-oriented electrical steel sheet may be any composition that allows secondary recrystallization to occur. When an inhibitor is used, for example, when an AlN-based inhibitor is used, appropriate amounts of Al and N may be contained, and when an MnS·MnSe-based inhibitor is used, appropriate amounts of Mn, Se and / or S may be contained. Of course, both inhibitors may be used in combination. In this case, the preferred contents of Al, N, S and Se are respectively as follows: Al: 0.010 to 0.065 mass%, N: 0.0050~0.0120mass%, S: 0.005 to 0.030 mass% and Se: 0.005~0.030mass% It is.

[0050] Furthermore, the present invention can also be applied to grain-oriented electrical steel sheets in which the contents of Al, N, S, and Se are limited and no inhibitor is used. In this case, the contents of Al, N, S, and Se are, respectively, Al: 0.010mass% or less, N: 0.0050mass% or less, S: 0.0050 mass% or less and Se:0.0050mass% or less It is preferable to suppress the

[0051] Representative basic components and optional added components applied to the steel material (slab) for the grain-oriented electrical steel sheet of the present invention will be specifically described below. C: 0.08mass% or less C is added to improve the hot-rolled sheet structure, but if the C content exceeds 0.08 mass%, it becomes difficult to decarburize to 50 mass ppm or less, at which magnetic aging does not occur during the manufacturing process, so the C content is preferably 0.08 mass% or less. Furthermore, since secondary recrystallization occurs even in steel materials that do not contain C, no lower limit for the C content is set.

[0052] Si: 2.0-8.0 mass% Silicon is an effective element for increasing the electrical resistance of steel and improving iron loss, but if the content is less than 2.0 mass%, the effect of improvement is not fully exerted, while if the content exceeds 8.0 mass%, the workability and threadability deteriorate significantly, and the magnetic flux density also decreases. Therefore, the Si content is preferably in the range of 2.0 to 8.0 mass%.

[0053] Mn: 0.005~1.0mass% Mn is an element necessary for improving hot workability, but if the content is less than 0.005 mass%, it is difficult to obtain this effect sufficiently. On the other hand, if the content exceeds 1.0 mass%, the magnetic flux density deteriorates. Therefore, the Mn content is preferably in the range of 0.005 to 1.0 mass%.

[0054] In addition to the above basic components, the following optional additive components, which are known to be effective in improving magnetic properties, may be appropriately contained. Ni: 0.03 to 1.50 mass%, Sn: 0.01 to 1.50 mass%, Sb: 0.005 to 1.50 mass%, Cu: 0.03 to 3.0 mass%, P: 0.03 to 0.50 mass%, Mo: 0.005 to 0.10 mass% and Cr: 0.03~1.50mass% One or more types selected from

[0055] Ni is an effective element for improving the hot-rolled sheet structure and magnetic properties. However, if the Ni content is less than 0.03 mass%, its contribution to magnetic properties is small, while if the Ni content exceeds 1.50 mass%, secondary recrystallization becomes unstable and magnetic properties deteriorate. Therefore, the Ni content is preferably in the range of 0.03 to 1.50 mass%.

[0056] In addition, Sn, Sb, Cu, P, Mo, and Cr are also elements that improve magnetic properties, but if the content is less than the lower limit, the effect is insufficient, and if the content exceeds the upper limit, the growth of secondary recrystallized grains is suppressed, resulting in deterioration of magnetic properties. Therefore, it is preferable to set each of these contents within the above range. In addition to the above components, the alloy consists of Fe and unavoidable impurities.

[0057] The steel material (slab) of the grain-oriented electrical steel sheet having the above-mentioned composition is hot-rolled and then hot-rolled annealed. Then, it is cold-rolled once or twice to finish it into a steel strip of the final thickness. The steel strip is then decarburized and annealed, coated with an annealing separator mainly composed of MgO, wound into a coil, and then subjected to final annealing for the purpose of secondary recrystallization and formation of a forsterite film. After the final annealing, the steel strip is subjected to flattening annealing, and a magnesium phosphate-based tension film is formed to produce the product steel strip.

[0058] In the present invention, a molten solidified portion is formed on the surface of the grain-oriented electrical steel sheet (steel strip) in an arbitrary step after cold rolling. The molten solidified portion is formed on one or both of the front and back surfaces of the steel sheet. [Melted and solidified part] The molten and solidified portion in the present invention is a surface layer (parent phase) of a grain-oriented electrical steel sheet that is partially melted and solidified by energy beam irradiation, etc. It is essential that this molten and solidified portion has a different component composition and magnetic permeability from those of the parent phase of the grain-oriented electrical steel sheet. Here, "having a different component composition from that of the parent phase of the grain-oriented electrical steel sheet" means a state in which components with a different magnetic permeability from that of the parent phase, which are not contained in the parent grain-oriented electrical steel sheet, are aggregated or dispersed in an area having a melted and resolidified structure different from that of the parent grain-oriented electrical steel sheet. Moreover, "having a magnetic permeability different from that of the parent phase of the grain-oriented electrical steel sheet" means that the maximum magnetic permeability is different from that of the grain-oriented electrical steel sheet parent phase in a hysteresis loop obtained using the Epstein method described in JIS C2550 or the SST method described in JIS C 2556. More specifically, it means that a component having a magnetic permeability different from that of the parent phase is mixed.

[0059] It should be noted that the magnetic domain refinement method using the molten solidified portion of the present invention can be combined with a conventional magnetic domain refinement method without any problem, and in that case, it is possible to achieve a high effect by combining the effects of both methods.

[0060] The molten solidified portion is a linear region extending continuously or discontinuously across the entire width of the steel sheet in a direction transverse to the rolling direction of the steel sheet, preferably within ±30° of the rolling direction. A large number of these molten solidified portions are arranged at intervals in the rolling direction of the steel sheet, and are used for magnetic domain refinement. The melt-solidified portion will be specifically described below.

[0061] <Components in the melted and solidified part that have a different magnetic permeability from the parent phase of the steel plate> ·Content rate: 5mass% or more and 40mass% or less As shown in the results of Experiment 1 above, even if the melted solidified portion contains a small amount of components whose magnetic permeability differs from that of the parent phase, the effect is achieved, but the content is preferably 5 mass% or more. In other words, when the magnetic permeability of the melted solidified portion decreases by 5% or more compared to that of the parent phase, it is believed that magnetic poles are formed at the phase interface and magnetic domain refinement occurs. According to the results shown in Figure 1, when the content of components whose magnetic permeability differs from that of the parent phase of the steel sheet becomes 5 mass% or more, the magnetic permeability decreases by 5% or more.

[0062] On the other hand, as shown in the results of Experiment 1 above, the component having a magnetic permeability different from that of the parent phase is preferably 40 mass% or less from the viewpoints of magnetic flux density and noise.

[0063] Ingredients The components with magnetic permeability different from that of the parent phase do not need to be particularly limited, but in addition to the typical examples of Ni, Co, Cr, Sn, Cu-Zn, Mg2SiO4, and SiO2 mentioned above, transition metals such as Cu and Al and their alloys, ceramics such as Al2O3, Si3N4, and TiN can be applied. In the typical examples above, the magnetic permeability is lower in non-magnetic metals (Cr, Sn, Cu-Zn) and ceramics (Mg2SiO4, SiO2) than in magnetic metals (Ni, Co), so it is advantageous to apply non-magnetic metals and ceramics for magnetic subdivision. Multiple types of these components may be used in combination.

[0064] <Dimensions of melted and solidified part> Width of melted and solidified part: 10μm to 300μm The width of the molten solidified portion, i.e., the width of each molten solidified portion in the rolling direction on the steel sheet surface, is preferably narrower because it can suppress deterioration of the magnetic permeability (magnetic flux density B8) of the entire steel sheet. Therefore, it is preferable to set it to 300 μm or less. On the other hand, if the width is excessively narrowed, the magnetic poles formed at both ends of the molten solidified portion will be bonded to each other, and the magnetic domain refining effect will decrease. Therefore, it is preferable to set it to 10 μm or more. More preferably, it is 20 μm or more and 250 μm or less.

[0065] Depth of molten solidification: 4% to 50% of plate thickness The deeper the molten solidified portion is formed, the more advantageous it is for improving iron loss. Therefore, it is preferable to make it 4% or more of the plate thickness of the steel plate. On the other hand, if it is made too deep, the plate threadability will be significantly deteriorated due to breakage caused by the molten solidified portion. Therefore, it is preferable to make it 50% or less of the plate thickness. More preferably, it is 5% or more and 45% or less.

[0066] - Formation interval in the rolling direction of the molten solidified part: 1mm to 10mm As shown in the results of Experiment 2 above, when magnetic properties and noise properties are taken into consideration overall, a thickness of 1 mm or more and 10 mm or less is preferable. -Measuring method for the spacing of molten solidified parts in the rolling direction The interval between the molten solidified portions in the rolling direction is the average value of the interval between the molten solidified portions adjacent to each other in the rolling direction. For example, a molten solidified portion is L0, and the Nth molten solidified portion existing in the rolling direction from L0 is L1. N When the distance between the molten and solidified parts is L p L0- and L N The distance between the molten solidified portions is the center-to-center distance in the rolling direction width of the molten solidified portions.

[0067] -Method of forming molten solidified part In order to form the molten solidified portion according to the present invention, a method of irradiating a laser or an electron beam as an energy beam can be mentioned, but the method is not limited to these methods, and any method can be used as long as it can input a sufficient amount of heat to melt the parent phase steel sheet. In addition to the laser and the electron beam, for example, a plasma flame or an arc discharge method can be used.

[0068] -Method of mixing components with different magnetic permeability from the steel sheet parent phase into the molten solidified part In the present invention, when forming the molten solidified portion, a metal element and / or ceramics having a component system with a magnetic permeability different from that of the parent phase of the grain-oriented electrical steel sheet is mixed in. Examples of the mixing method include a method of forming a layer of a predetermined component on the steel sheet surface by electrodeposition, vapor deposition, or chemical reaction, and irradiating an energy beam from above the layer of the predetermined component, or a method of placing a wire of a predetermined component system on the steel sheet surface and irradiating an energy beam, but are not limited to these methods.

[0069] -Method of measuring the content of components with different magnetic permeability from the steel plate parent phase in the molten solidified part The content of components in the molten solidified part that have a different magnetic permeability from the steel sheet matrix is ​​measured using an electron probe microanalyzer (EPMA). That is, in the molten solidified part, quantitative analysis is performed on the component elements of the steel sheet matrix and the mixed component elements, and the content of the components that have a different magnetic permeability from the steel sheet matrix is ​​calculated in mass% from the area of ​​the molten solidified part and the atomic weight and molecular weight of each element.

[0070] -Method for measuring magnetic permeability of molten and solidified parts In the present invention, it is preferable that the magnetic permeability of the molten solidified portion is lower than that of the parent phase of the steel sheet. Since it is difficult to directly measure the magnetic permeability of the molten solidified portion in the present invention, the relative magnetic permeability to the parent phase of the steel sheet is calculated by the following method and used as an index of the magnetic permeability of the molten solidified portion. That is, in the grain-oriented electrical steel strip in which the molten solidified portion according to the present invention is partially formed, a sample taken from a portion in which the molten solidified portion is not formed is subjected to hysteresis loop measurement by the Epstein method described in JIS C2550. From the hysteresis loop obtained here, the maximum magnetic permeability μ in the initial magnetization curve is calculated. m、p Similarly, a hysteresis loop is measured for a sample taken from the portion where the molten solidified portion was formed. The maximum magnetic permeability μ m、m Calculate the maximum magnetic permeability μ m、p Maximum permeability μ m、m The relative permeability μ r is used as an index of magnetic permeability of the molten and solidified portion. However, when used in combination with the non-heat-resistant magnetic domain refining method, the measurement is performed using the SST method described in JIS C 2556.

[0071] -Angle between extension direction of molten solidified part and rolling direction: Within ±30° The more the linear extension direction of the molten solidified portion is inclined from the rolling direction (sheet width direction), the fewer the magnetic poles generated at the interface between the closure domain and the main domain, and the worse the domain refinement effect. Therefore, it is preferable that the angle between the extension direction of the molten solidified portion and the rolling direction is within ±30°.

[0072] Next, the energy beam irradiation method according to the present invention will be described. When forming the molten solidified portion, a laser having a wavelength of 400 nm to 1200 nm, which has a high absorption rate in metal, can be used, and it is also effective to use an electron beam with high penetrating power.

[0073] [Electron beam] The preferred electron beam irradiation conditions that are advantageous for forming the molten solidified portion of the present invention will be described in more detail below. Acceleration voltage: 60kV to 300kV The higher the acceleration voltage, the more linear the electrons will travel and the less the thermal effect on the outside of the beam irradiation area will be, which is preferable. For these reasons, the acceleration voltage is preferably 60 kV or more, more preferably 90 kV or more, and even better 120 kV or more. On the other hand, if the acceleration voltage is too high, it becomes difficult to block the X-rays generated by the electron beam irradiation. Therefore, from a practical standpoint, it is preferable to set the acceleration voltage to 300 kV or less, and more preferably 200 kV or less.

[0074] Beam current: 0.5 mA to 40 mA From the viewpoint of beam diameter, it is preferable that the beam current is small. This is because if the current is large, the beam diameter is likely to expand due to Coulomb repulsion. Therefore, in the present invention, it is preferable that the beam current is 40 mA or less. On the other hand, if the beam current is too small, the energy required to form distortion will be insufficient. Therefore, it is preferable that the beam current is 0.5 mA or more.

[0075] - Vacuum level in the beam irradiation area The electron beam is scattered by gas molecules, which causes an increase in the beam diameter and halo diameter, a decrease in energy, etc. Therefore, the degree of vacuum in the beam irradiation area is better, and it is desirable to set the pressure at 3 Pa or less. There is no particular lower limit, but if it is lowered too much, the cost of the vacuum system, such as the vacuum pump, will increase. Therefore, in practice, it is recommended to set the lower limit at 10 -5 It is preferable to set the pressure at 1 Pa or more.

[0076] [Laser beam] In addition, the preferable conditions for irradiating the laser, which are advantageous for forming the molten solidified portion of the present invention, will be described in detail. Laser output: 50W or more and 5000W or less When the laser output is low, the scanning speed must be slowed down to melt the steel plate. In this case, if the speed is slowed down too much, the space factor will decrease due to the scattering of spatter on the steel plate, and manufacturing efficiency will deteriorate. On the other hand, if the output is high, it will be easier to melt the steel plate, but damage to the laser transport system will increase, and maintenance frequency will increase, resulting in lower manufacturing efficiency. From these points of view, it is desirable to set the laser output to between 50W and 5000W.

[0077] Spot diameter: 300μm or less The smaller the spot diameter, the more localized the distortion can be introduced, which is preferable. Therefore, in the present invention, the beam diameter of the energy beam is preferably 300 μm or less. It is more preferable to set it to 280 μm or less, and even more preferable to set it to 260 μm or less. Here, the spot diameter refers to the full width at half maximum of the beam profile obtained by the slit method using a slit with a width of 30 μm.

[0078] ·Deflection speed: 5~400m / s The slower the deflection speed of the beam, the more heat can be incident on the steel plate per unit length, so a slower deflection speed is preferable. However, if the speed is too slow, metal vapor will fly off and cause spatter to adhere to the surface of the steel plate, degrading the space factor when laminated as an iron core. For this reason, the deflection speed should be 5 m / s or more. Also, if the speed is too high, a power supply capacity is required to provide the heat input required to melt the steel plate, leading to an increase in the size of the equipment. Therefore, a deflection speed of 400 m / s or less is preferable.

[0079] In the present invention, other than the steps and manufacturing conditions described above, a known manufacturing method for a grain-oriented electrical steel sheet can be appropriately used. EXAMPLES

[0080] Next, the present invention will be specifically described based on the examples. The following examples are preferred examples of the present invention, and the present invention is not limited to these examples. The present invention can be modified within the scope of the present invention, and such modifications are also included in the technical scope of the present invention.

[0081] A slab for grain-oriented electrical steel containing the components shown in Table 1 is hot-rolled, annealed, and then cold-rolled twice with intermediate annealing to obtain a cold-rolled steel strip with a thickness of 0.23 mm. This cold-rolled steel strip is divided into two at the center in the sheet width direction, and various metal elements or ceramics are electrodeposited on a part of one of the steel strips, and a laser or electron beam is irradiated toward these electrodeposited films to form a melted and solidified part. For some metals and alloys, wires (0.1 mmφ) are prepared, the wires are arranged linearly on the surface of the non-electrodeposited part of the steel strip, and a laser or electron beam is irradiated from above each wire to form a melted and solidified part. In addition, a laser or electron beam is irradiated to a part of a part where nothing is electrodeposited, and the part is melted and solidified. For the other steel strip, a resist ink is applied to the entire steel plate, and then a non-masked part is formed by laser irradiation. This steel strip is subjected to electrolytic etching to form a groove. Ni or Fe-Ni alloy was electrodeposited on a part of this coil, and Ni or Fe-Ni alloy was filled in the grooves. At this time, the intervals between the melted and solidified parts or the grooves were 4 mm, and each had a depth of 20 μm and a width of 80 μm.

[0082] After removing the electrodeposit remaining on the cold-rolled steel strip, the steel strip was decarburized, coated with an annealing separator mainly composed of MgO, wound into a coil, and then subjected to final annealing. The steel strip after the final annealing was subjected to flattening annealing, and then a magnesium phosphate-based tension coating was formed to obtain the final product steel strip. In addition, a groove or local strain was formed in a part of the formation area of ​​the molten solidification part at a position that does not overlap with the molten solidification part. Furthermore, for comparison, a sample in which only a groove or local strain was formed in a part where the molten solidification part was not formed was also prepared.

[0083] [Table 1]

[0084] Samples were cut out from the steel strips thus produced for each of the above treatments, and the B8 of each sample was measured by the SST method. The change in magnetic flux density B8, ΔB8 (=BA), was calculated from B8(A) of the sample cut out from the area where no groove, local strain, or molten solidified area was formed, and B8(B) of each sample cut out from the area where groove or local strain, molten solidified area, and molten solidified area + groove or local strain were formed. In addition, a three-phase winding transformer (iron core weight 500 kg) was produced from each steel strip, and the iron loss characteristics were measured when the magnetic flux density of the iron core leg part was 1.7 T at a frequency of 50 Hz. The no-load loss of the iron loss characteristics at 1.7 T and 50 Hz was measured using a wattmeter. At the same time, this model transformer was excited in a soundproof room under the conditions of maximum magnetic flux density Bm = 1.7 T and 50 Hz, and the sound level (dBA) was measured using a sound level meter. In addition, for the samples to which local strain had been introduced, stacked cores of the same weight were fabricated and similar evaluations were performed.

[0085] The above evaluation results are summarized in Table 2. In both samples where the molten solidified portion was created using the laser or electron beam method, a significant iron loss improvement effect was confirmed compared to samples where only the steel plate was melted, due to the formation of a molten solidified portion in which metals, alloys or ceramics were mixed into the molten portion. Furthermore, the iron loss improvement effect was greater in the electron beam irradiated sample than in the laser irradiated sample. This is thought to be due to the difference in the form of heat input, i.e., with laser irradiation the steel plate melts from the surface, whereas with electron beams the steel plate melts from the inside, changing the distribution of components different from the parent phase. On the other hand, the sample with only the grooves shows a large degradation of B8, and the sample with the grooves filled with magnetic metal suppresses the degradation of B8, but the noise level increases due to the strain caused by the difference in lattice constant with the parent phase. In this regard, the sample according to the present invention suppresses the degradation of both B8 and noise, demonstrating the superiority of the present invention.

[0086] [Table 2] EXAMPLES

[0087] A slab for grain-oriented electrical steel containing the components shown in Table 1 was hot-rolled, annealed, and then cold-rolled twice with intermediate annealing to obtain a cold-rolled steel strip with a thickness of 0.23 mm. In a part of this cold-rolled steel strip, Ni, Cu-Zn, and SiO2 were electrodeposited at different locations, and an electron beam was irradiated toward these electrodeposited films to form a molten solidified portion. At the same time, an electron beam was irradiated to a part of an area where nothing was electrodeposited, and the steel sheet was melted. At this time, the formation interval and formation pattern of the molten solidified portion were variously changed, and each depth was 30 μm and width was 100 μm.

[0088] After removing the electrodeposits remaining on the cold-rolled steel strips, the steel strips were subjected to decarburization annealing, coated with an annealing separator mainly composed of MgO, wound into a coil, and then subjected to final annealing. After the final annealing, the steel strips were subjected to flattening annealing, and then a magnesium phosphate-based tension coating was formed to produce the final product steel strips.

[0089] Samples were cut out from the steel strip thus produced for each of the above treatments, and the B8 of each sample was measured by the Epstein method. The change in magnetic flux density B8, ΔB8 (=BA), was calculated from B8(A) of the sample irradiated with the electron beam in the area without the electrochemical deposition (non-electrochemical portion) and B8(B) of the sample cut out from the area where the molten solidified portion was formed (electrochemical portion).

[0090] Furthermore, the hysteresis loop of the same sample was measured, and the maximum magnetic permeability in the initial magnetization curve was measured. The ratio μ r (=μelectrodeposited part / μnon-electrodeposited part) was calculated as an index of magnetic permeability change. After magnetic measurement, each sample was embedded in a carbon mold and mirror-polished, and the cross section of the molten solidified part was observed with an EPMA to analyze the electrodeposits and other components (the same components as the parent phase grain-oriented electrical steel sheet), and the content was calculated.

[0091] In addition, a three-phase wound transformer (core weight 500 kg) was made from each steel strip, and the iron loss characteristics were measured when the magnetic flux density in the core legs was 1.7 T at a frequency of 50 Hz. The no-load loss of the iron loss characteristics at 1.7 T and 50 Hz was measured using a wattmeter. At the same time, this model transformer was excited in a soundproof room under the conditions of maximum magnetic flux density Bm = 1.7 T and frequency of 50 Hz, and the noise level (dBA) was measured using a sound level meter.

[0092] The above evaluation results are summarized in Table 3. In the samples in which a component different from the parent phase was mixed in the steel plate fusion zone, μ r A decrease in the amount of the molten metal was confirmed, and an improvement in the characteristics was confirmed under the same conditions. In particular, it can be seen that when the content, the formation interval and the formation pattern of the molten solidified portion are within the preferable conditions of the present invention, particularly excellent characteristics are expressed.

[0093] [Table 3]

Claims

1. A grain-oriented electrical steel sheet having a molten solidified portion extending in a direction transverse to the rolling direction of the steel sheet on at least one of the front and back surfaces of the grain-oriented electrical steel sheet, wherein the molten solidified portion has a component composition and magnetic permeability different from those of a parent phase of the grain-oriented electrical steel sheet, and the ratio of the magnetic permeability of the molten solidified portion to the magnetic permeability of the parent phase is 0.95 or less.

2. The grain-oriented electrical steel sheet according to claim 1 , wherein the molten solidified portion contains a component having a magnetic permeability different from that of the parent phase.

3. The grain-oriented electrical steel sheet according to claim 1 or 2, wherein the molten solidified portion contains one or more metal elements different from the parent phase.

4. The grain-oriented electrical steel sheet according to claim 1 , wherein the molten solidified portion contains a ceramic compound.

5. The grain-oriented electrical steel sheet according to any one of claims 2 to 4, wherein the molten solidified portion has a content of a component having a magnetic permeability different from that of the parent phase of 5 mass% or more and 40 mass% or less.

6. The molten solidified portion is formed periodically in the rolling direction, and the interval between the molten solidified portions in the rolling direction is 1 mm or more and 10 mm or less.

7. The grain-oriented electrical steel sheet according to claim 1 , wherein the molten solidified portion is linear.

Citation Information

Patent Citations

  • Device for straining steel plate

    JP1987086121A

  • Production of grain-oriented silicon steel sheet excellent in magnetic property

    JP1993186827A

  • Small sized panhead device

    JP1994022179A

  • Low iron loss grain-oriented silicon steel sheet and its production

    JP1994212275A

  • Manufacture of low iron-loss grain oriented silicon steel plate and plasma generating device

    JP1995192891A